Exploring healthcare experiences of transgender people in the Jabula Uzibone study, South Africa: a longitudinal implementation science study - Rutendo Bothma; Audrey Pettifor; Innocent Maphosa; Philisiwe Ndlovu; John Imrie; Tonia Poteat (Journal of the International AIDS Society)
Abstract Introduction The World Health Organization promotes a transgender‐differentiated service delivery (TG‐DSD) model to overcome barriers to HIV service engagement among transgender people (TGP). For TGP, an essential element of DSD includes gender‐affirming care which is non‐stigmatising, free from discrimination and celebrates their gender identity. The Jabula Uzibone Study, launched in November 2023, assesses the cost and effectiveness of TG‐DSD on HIV outcomes. In this paper, we describe the baseline characteristics of TGP in our study and explore whether there are differences in healthcare experiences among those seeking care at TG‐DSD clinics versus standard service delivery (SSD) clinics at baseline. Methods This observational, mixed‐method, prospective implementation study compares models of care at four TG‐DSD and four SSD facilities using standardised observation checklists, in‐depth and key informant interviews. For this paper, we asked participants about healthcare experiences and experiences of stigma through a structured, interviewer‐administered quantitative survey. We assessed the sections of the quantitative survey which ask about self‐reported experiences of stigma. Results The study enrolled 422 TGP with HIV (217 TG‐DSD and 205 SSD) and 248 TGP without HIV (128 TG‐DSD and 120 SSD); 15% (102/670) gender non‐conforming, 15% (91/670) TG men and 70% (477/670) TG women. Participants’ median age was 29 years, interquartile range: 24−35 years. SSD participants at baseline were 46% more likely to experience stigma compared to their TG‐DSD counterparts (aOR = 1.46, 95% CI: 1.06, 2.01). SSD participants were more likely to encounter a healthcare provider who is unwilling to provide care for them (aOR = 1.55, 95% CI: 1.09, 2.21) and to report that healthcare workers are unable to provide the same quality care to TGP as they do other people (aOR = 1.46, 95% CI: 1.00, 1.91) compared to their TG‐DSD counterparts. Conclusions TGP from TG‐DSD facilities were less likely to report experiences of facility‐based enacted stigma at baseline, compared to the TGP from SSD facilities. Our study highlights the importance of provider training in tailored transgender healthcare to provide gender‐affirming healthcare services. Results from the Jabula Uzibone study will provide further evidence of the effectiveness of TG‐DSD models in sub‐Saharan Africa, and the role of stigma and discrimination in HIV outcomes among TGP.